DNA Hypermethylation of Promoter of Gene p53 and p16 in Arsenic-Exposed People with and without Malignancy - Chanda, Sarmishtha; Dasgupta, Uma B.; GuhaMazumder, Debendranath; Gupta, Mausumi; Chaudhuri, Utpal; Lahiri, Sarbari; Das, Subhankar; Ghosh, Nilima; Chatterjee, Debdutta (Toxicological sciences, 2006)
Chronic arsenic exposure is known to produce arsenicosis and cancer. To ascertain whether perturbation of methylation plays a role in such carcinogenesis, the degree of methylation of p53 and p16 gene in DNA obtained from blood samples of people chronically exposed to arsenic and skin cancer subjects was studied. Methylation-specific restriction endonuclease digestion followed by polymerase chain reaction (PCR) of gene p53 and bisulfite treatment followed by methylation-sensitive PCR of gene p16 have been carried out to analyze the methylation status of the samples studied. Significant DNA hypermethylation of promoter region of p53 gene was observed in DNA of arsenic-exposed people compared to control subjects. This hypermethylation showed a dose-response relationship. Further, hypermethylation of p53 gene was also observed in arsenic-induced skin cancer patients compared to subjects having skin cancer unrelated to arsenic, though not at significant level. However, a small subgroup of cases showed hypomethylation with high arsenic exposure. Significant hypermethylation of gene p16 was also observed in cases of arsenicosis exposed to high level of arsenic. In man, arsenic has the ability to alter DNA methylation patterns in gene p53 and p16, which are important in carcinogenesis.